2006
DOI: 10.1111/j.1440-6055.2006.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

The hymenopteran parasitoids of light brown apple moth, Epiphyas postvittana (Walker) (Lepidoptera: Tortricidae) in Australia

Abstract: Epiphyas postvittana (Walker) is a serious pest of a number of horticultural crops including grapes in Australia and New Zealand. This study brings together information on the parasitoid complex associated with E. postvittana that previously was fragmented and largely inaccessible. We include species reared during a 3-year study of the parasitoids of E. postvittana in the vineyards of the Coonawarra region, South Australia, material from several Australian agricultural insect collections and records from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…High toxicity loads, quantified by the cumulative pesticide metric in vineyards, adversely affected specific canopy arthropod taxa. Negative effects were detected for two taxa of parasitoids that include species important in controlling light-brown apple moth (Paull and Austin 2006). They also included predatory beetle taxa known to feed on mealybugs and likely to prey on aphids as well as the immature stages of moth pests including eggs.…”
Section: Discussionmentioning
confidence: 99%
“…High toxicity loads, quantified by the cumulative pesticide metric in vineyards, adversely affected specific canopy arthropod taxa. Negative effects were detected for two taxa of parasitoids that include species important in controlling light-brown apple moth (Paull and Austin 2006). They also included predatory beetle taxa known to feed on mealybugs and likely to prey on aphids as well as the immature stages of moth pests including eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Sticky traps were in place for 6–8 days at the start of each month between October 2011 and February 2012 (five collections). Arthropods trapped on yellow sticky traps were assessed under a dissecting microscope when attached to the sticky traps at magnifications of × 20 to × 100 using several taxonomic resources (CSIRO, ; Glenn et al , ; Paull & Austin, ; Stevens et al , ) with hymenopterans sorted to family level. To assess the size of the Hymenoptera families, the mean length of 10 randomly selected individuals from each family was measured; families less than 2 mm were classed as small, 2–3 mm as intermediate and >3 mm as large.…”
Section: Methodsmentioning
confidence: 99%
“…The role of parasitoids other than Trichogrammatidae is largely unknown. However, many other parasitoids have a role in control of mealybugs, scale and light brown apple moth ( Thomson & Hoffmann, 2006a ) and a recent study by Paull and Austin (2006) revealed 25 larval and pupal parasitoids of light brown apple moth.…”
Section: Discussionmentioning
confidence: 99%